Features of forming an invertebrate fauna in technogen environment (Kriviy Rig, Ukraine) - Kul'Bachko, Y.; Pakhomov, O.; Didur, O.; Loza, I. (Acta Agraria Debreceniensis, 2016)
The features of invertebrate fauna forming in conditions of technogen pressure (Kriviy Rig, Ukraine) were studied. The taxonomic composition, dominance structure and correlation of soil invertebrates’ functional groups in the large industrial enterprises were examined. It had been found that a small thickness of the soil layer as a habitat for ground animals causes the depletion of taxonomic composition, species richness and decrease the total number of soil invertebrates. Gastropoda molluscs in conditions of technogen pressure are the most adapted to stresses group of invertebrates.